Producción de pepino (Cucumis sativus L), tutorado y sin tutorar con dos abonos orgánicos - Silva Torres, Jorge Raúl (2015)
Experimental development to continue the hybrid (Cucumis sativus L.), Tutoring Marketmore without mentorship with two organic fertilizer, to measure the production of cucumber, two Algasoil manure and Vermicompost, without applying fertilizers three replicates per experiment the thesis project is the development in the province of Los Ríos Region Valencia with a geographical location 1 3'18'' south latitude and 79 ° west longitude 25'29'' at a height of 73 meters. With a rainfall precipitation 2400 mm / year with a temperature of 21-31 ° C, The experimental design would apply for plots with 6 replicates of each treatment and 3 witnesses, plants for the study variables were evaluated with Tukey analysis Alfa with a probability of 95% for research variables were taken germination, male, female, plant height, fruit diameter, length of fruit, fruit weight and number of fruits by the five crops that were representative for the analysis of research and data collection that allowed establishing the influence of culture bloom tutoring and mentorship without the hybrid under study. Thus the experimental plots for the development of hybrid Marketmore, T1 (Tutoring fertilizer), T2 (tutored Vermicompost), T3 (tutored Algasoil), T4 were established (No mentorship without fertilizers), T5 (No mentorship Humus earthworm), T6 (no mentorship Algasoil). Economic study was conducted to determine the levels of profitability and demonstrate which of fertilizers both Algasoil as vermicompost without fertilizer had the most suitable for the development of hybrid cucumber cultivation Marketmore features. Resulting in the Treatment 2 (Tutoring with Algasoil) is higher profitability rate of 1.38 kg of fertilizer per plant, followed by Treatment 2 (tutoring Vermicompost) with a percentage composted 0.60 kg per plant.